Perception of sound rotation velocity: The effect of sound type and measurement method - Bor Sojar Voglar (Psihološka Obzorja, 2006)
Vestibular suppression is a phenomenon where the vestibular information is suppressed when a contradictory visual stimulation is present. The aim of the present study was, before conducting a study that would examine whether vestibular suppression can also occur while exposed to sound stimuli, to discover how changes in sound rotation velocity are perceived and what method could yield valid measures of the percepts. An experiment was conducted with 40 participants with normal hearing. Participants were divided into 4 groups in which 2 sound properties (sinusoid wave and speech) and 2methods (adopted global perception method and graph method) were used separately. Sound rotated around participants and changed the velocity. Participants had to report whether they perceived the velocity as constant, accelerated, or decelerated, or they had to draw a graph to indicate their perception. It was found that constant velocity is perceived as slightly decelerated, and this bias in velocity perception was larger with sine sound than with speech, but speech as a property of rotating sound stimulus seems to be too complex. The graph method was very hard for participants to use, and we therefore discourage the use of this method in future. Future studies should use the "estimation-of-change-in-given-time-interval" method and vary the sound rotation velocity in random order.